2014
DOI: 10.1177/0011000014548898
|View full text |Cite
|
Sign up to set email alerts
|

Educating Undergraduate Students to Work With Children of Abused Women

Abstract: Student learning was assessed in an innovative university-community partnership in which undergraduate students enrolled, first, in a didactic course on intimate partner violence and, subsequently, in a service-learning course where they worked with children living in a shelter for survivors of intimate partner violence. Data were collected at the start and end of the first semester, and at the end of the second semester. Quantitative and qualitative methods indicated that students gained knowledge regarding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A. Goodman et al, 2004; Nilsson et al, 2011; Singh et al, 2010). In response, a two-volume issue of The Counseling Psychologist was published in 2014 as a way to highlight innovative strategies that implement nontraditional approaches to SJ training (e.g., see Ali & Sichel, 2014; Motulsky et al, 2014; O’Brien et al, 2014; Toporek & Worthington, 2014). Using a liberation psychology lens, and in alignment with those in the field who push for nontraditional approaches, we propose it is time to move beyond the conceptualization of nontraditional pedagogical approaches to MC and SJ and begin to focus on how to integrate them into training programs.…”
Section: Recommendations For Instructors and Graduate Training Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…A. Goodman et al, 2004; Nilsson et al, 2011; Singh et al, 2010). In response, a two-volume issue of The Counseling Psychologist was published in 2014 as a way to highlight innovative strategies that implement nontraditional approaches to SJ training (e.g., see Ali & Sichel, 2014; Motulsky et al, 2014; O’Brien et al, 2014; Toporek & Worthington, 2014). Using a liberation psychology lens, and in alignment with those in the field who push for nontraditional approaches, we propose it is time to move beyond the conceptualization of nontraditional pedagogical approaches to MC and SJ and begin to focus on how to integrate them into training programs.…”
Section: Recommendations For Instructors and Graduate Training Programsmentioning
confidence: 99%
“…Recent scholarship from the United States exploring the implementation of an SJ practicum in counseling psychology offered a preliminary framework that begins to delve into the multitude of opportunities, obstacles, and challenges of applying SJ components to clinical practice (Hage et al, 2020). Other scholars have suggested incorporating SJ into pedagogical approaches by giving students the opportunity to be involved in community projects, practicums/internships, and in-service learning courses (e.g., Ali & Sichel, 2014; O’Brien et al, 2014). However, there is still a need for empirical evaluation to better understand the types of undertakings that promote SJ in a contextual way (Hage et al, 2020).…”
Section: Recommendations For Instructors and Graduate Training Programsmentioning
confidence: 99%
“…Consistent with previous service-learning research, peer mentors and staff alike in this case observed multiple positive impacts on mentors' personal and professional development as a result of course participation. The broadened perspectives, personal and professional growth through experience, opportunities to learn and practice soft skills and advocacy, and the increased ability to connect what mentors learned in the classroom with their mentoring are all characteristic of service-learning in general (Conway et al, 2009;Jacoby, 2003;Nikels et al, 2007;O'Brien et al, 2014;Peterson, 2009;Rutti et al, 2015). In addition, the intentionality with which staff structured the course itself created an atmosphere fostering connection and reflection for mentors.…”
Section: Discussionmentioning
confidence: 99%
“…Service-learning instruction, often associated with the work of John Dewey, was first introduced in the early 1990s and is increasingly used as a pedagogical strategy within educational settings (Giles & Eyler, 1994). Researchers have described service-learning as an experiential teaching strategy in which faculty and students engage with a community to meet identified needs (Midgett, Hausheer, & Doumas, 2016;O'Brien, Risco, Castro, & Goodman, 2014;Weiler et al, 2013). Service-learning instruction has proven effective in increasing understanding of specified populations while offering opportunities to connect directly with groups in need (Conway, Amel, & Gerwien, 2009;O'Brien et al, 2014).…”
Section: Peer Mentoring As Service-learningmentioning
confidence: 99%
“…However, applied psychology remains at the early stages of expanding clinical training to incorporate social justice advocacy: Much of the training literature has focused on general, nonapplied principles, definitions, and competencies (Koch & Juntuenen, 2014; Motulsky, Gere, Saleem, & Trantham, 2014). Existing works focus almost exclusively on practicum (Burnes & Ross, 2010; Hoover & Morrow, 2016), service learning (O’Brien, Risco, Castro, & Goodman, 2014; Toporek & Worthington, 2014), and overall training programs (Mallinckrodt, Miles, & Levy, 2014; Motulsky et al, 2014). Little current literature focuses on how to integrate social justice principles and practice throughout coursework, particularly group psychotherapy training.…”
mentioning
confidence: 99%